Does perceived organization support moderates the relationships between work frustration and burnout among intensive care unit nurses? A cross-sectional survey - Ren Yanbei; Ma Dongdong; Liu Yun; Wu Ning; Qin Fengping (BMC, 2023)
Abstract Background Intensive care unit (ICU) nurses are at high risk of burnout and warranting attention. Existing literature found that work frustration was related to burnout, whilst perceived organization support influenced the association of work frustration with burnout. The purpose of this study was to investigate the relationship of work frustration and burnout among ICU nurses, and to examine the moderating effect of perceived organization support in their relationship. Methods The cross-sectional study was conducted with a convenience sample of 479 ICU nurses from several 3 tertiary hospitals during December 2021 to May 2022. The Maslach Burnout Inventory-Human services survey (MBI-HSS), National Aeronautics and Space Administration Task Load Index (NASA-TLX) and perceived organization support Scale (POSS) were used to collect data. The PROCESS macro was performed to test the moderation effect of perceived organization support. Results The total score of burnouts was (55.79 ± 17.20), the total score of work frustration was (7.44 ± 1.86). Burnout was positively correlated with work frustration (r = 0.301, P < 0.001) and negatively correlated with perceived organizational support (r = -0.430, P < 0.001). The moderation model analysis showed that perceived organizational support could moderate the relationship between work frustration and burnout (β = -0.111, ΔR2 = 0.011, P = 0.007). Conclusions The findings highlight the moderating role of perceived organizational support in the relationship between work frustration and burnout. Hence, interventions to reduce burnout among ICU nurses should consider targeting organizational support and work frustration.